SOCIAL PHENOMENON OF PRE WEDDING PHOTO TRENDS AT DENPASAR COMMUNITY WEDDING CEREMONY - Kartika Pratiwi, AA PT Candra; Suastika, I Made; Kebayantini, Ni Luh Nyoman (E-Journal of Cultural Studies; Vol 14 No 4 (2021): Volume 14, Number 4, November 2021DO - 10.24843/cs.2021.v14.i04.p05, 2021)
The social phenomenon of pre-wedding photos has now begun to be widely discussed by some people who are starting to be sensitive to social changes in the area of Denpasar City. Infact, in Denpasar City at this time almost all bride and groom couples carry out pre-wedding photo sessions before their wedding ceremony takes place. The bride and groom couples even really focus their attention on the results of their pre-wedding photos. This eventually became a conversation that raised pros and cons among parents whose children were going to have a wedding ceremony. Some parents feel that pre-wedding photos cost too much money and costs that they should be able to spend to bail out funds when preparing a series of wedding ceremonies. In contrast to people who feel capable in terms of costs, they will certainly take the pre-wedding costs lightly compared to the satisfaction they will get later after seeing the results of the pre-wedding photos they take. The bride and groom did a pre-wedding photo session with the theme and concept they specified. When going to do a pre-wedding photo session, the bride and groom have to prepare a lot of money. Depending on the theme, concept and place they will use later. In Bali, especially in Denpasar City, the cost for the “pawiwahan”or wedding ceremony is quite high, with the addition of a new tradition, namely pre-wedding photos, it will make people spend even more. The meaning of this pre-wedding photo session is still not much can explain, prospective brides who do pre-wedding photo sessions only say they take pre-wedding photos to follow today's trends. The new trend that is entering Bali is slowly making it a mandatory tradition. Keywords: pre wedding photo, wedding ceremony, trends, traditions